The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/apt.17513
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: Post‐COVID‐19 functional dyspepsia and irritable bowel syndrome

Abstract: Summary Introduction The burden of post‐COVID‐19 functional dyspepsia (FD) and irritable bowel syndrome (IBS) remains unclear. The aim of this meta‐analysis was to estimate the rate of post‐COVID‐19 FD and IBS. Methods MEDLINE, Scopus and Embase were searched through 17 December 2022. Studies reporting the incidence of FD and/or IBS in COVID‐19 survivors and controls (without COVID‐19), when available, according to the Rome criteria, were included. Estimated incidence with 95% confidence intervals (CI) was poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
(183 reference statements)
0
2
0
1
Order By: Relevance
“…Факторы, значимо связанные с диагнозом СРК, включали аллергию в анамнезе (ОШ 10,024, 95% ДИ 1,766-56,891), хронический прием ингибиторов протонной помпы (ОШ 4,816, 95% ДИ 1,447-16,025) и наличие одышки (ОШ 4,157, 95% ДИ 1,336-12,934). Проведенный позже метаанализ, объединивший данные 10 исследований и 2763 пациентов с COVID-19, показал, что распространенность ПИ-СРК у лиц, перенесших инфекцию, составляет 12% (95% ДИ 8-16), а объединенное ОШ развития СРК, учитывая только исследования с проспективной когортой (три исследования) -12,92, 95% ДИ 3,58-46,60 [79].…”
Section: перенесенные окиunclassified
“…Факторы, значимо связанные с диагнозом СРК, включали аллергию в анамнезе (ОШ 10,024, 95% ДИ 1,766-56,891), хронический прием ингибиторов протонной помпы (ОШ 4,816, 95% ДИ 1,447-16,025) и наличие одышки (ОШ 4,157, 95% ДИ 1,336-12,934). Проведенный позже метаанализ, объединивший данные 10 исследований и 2763 пациентов с COVID-19, показал, что распространенность ПИ-СРК у лиц, перенесших инфекцию, составляет 12% (95% ДИ 8-16), а объединенное ОШ развития СРК, учитывая только исследования с проспективной когортой (три исследования) -12,92, 95% ДИ 3,58-46,60 [79].…”
Section: перенесенные окиunclassified
“…We read with interest the recent meta-analysis of 10 studies exploring the prevalence of functional dyspepsia (FD) and irritable bowel syndrome (IBS) in individuals following COVID-19 infection. 1 Marasco et al highlight a significantly higher prevalence of IBS in post-COVID-19 patients compared with controls, and a higher risk of developing IBS in patients with severe COVID-19. This study contributes to the existing data on gastrointestinal (GI) manifestations of Long COVID, a newly minted entity which continues to evolve.…”
Section: Editorsmentioning
confidence: 99%
“…Interestingly, it has been observed that patients previously diagnosed with COVID-19 are at greater risk of developing Irritable Bowel Syndrome (IBS) when compared with uninfected individuals 7 . IBS, in turn, is one of the Gut-Brain Interaction Disorders (GBID), previously called Functional Gastrointestinal Disorders (FGD) 8 .…”
Section: Eligibility Criteriamentioning
confidence: 99%